2017
DOI: 10.1002/2017jd026660
|View full text |Cite
|
Sign up to set email alerts
|

Tree ring δ18O reveals no long‐term change of atmospheric water demand since 1800 in the northern Great Hinggan Mountains, China

Abstract: Global warming will significantly increase transpirational water demand, which could dramatically affect plant physiology and carbon and water budgets. Tree ring δ18O is a potential index of the leaf‐to‐air vapor‐pressure deficit (VPD) and therefore has great potential for long‐term climatic reconstruction. Here we developed δ18O chronologies of two dominant native trees, Dahurian larch (Larix gmelinii Rupr.) and Mongolian pine (Pinus sylvestris var. mongolica), from a permafrost region in the Great Hinggan Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The strong correlations between oxygen and carbon isotopic records of Q. petrea , F. sylvatica , and P. sylvestris and summer temperature and air moisture (VPD, RH, and PET) indicated that all these climate variables are potential targets for long‐term reconstructions. While VPD plays a critical role in controlling ecosystem fluxes of water and carbon (Novick et al, ; Sulman et al, ), its long‐term changes have not been documented (to our knowledge only one reconstruction by Liu et al, ). Our results thus open the door to new VPD‐based environmental reconstructions in temperate areas.…”
Section: Discussionmentioning
confidence: 94%
“…The strong correlations between oxygen and carbon isotopic records of Q. petrea , F. sylvatica , and P. sylvestris and summer temperature and air moisture (VPD, RH, and PET) indicated that all these climate variables are potential targets for long‐term reconstructions. While VPD plays a critical role in controlling ecosystem fluxes of water and carbon (Novick et al, ; Sulman et al, ), its long‐term changes have not been documented (to our knowledge only one reconstruction by Liu et al, ). Our results thus open the door to new VPD‐based environmental reconstructions in temperate areas.…”
Section: Discussionmentioning
confidence: 94%
“…Dry air (reduced relative humidity and increased VPD) causes a strong degree of the 18 O enrichment in leaf water through transpiration, thereby producing high tree-ring δ 18 O [12,13]. Leaf δ 18 O enrichment in Larix is expected to be controlled by the water availability, which in turn is usually controlled by the VPD [46,47]. The high explained variance in VPD reconstruction at the FOD scale further illustrates the controls of VPD on tree-ring δ 18 O (Figure 8).…”
Section: Climate Drivers Of Tree's Physiologymentioning
confidence: 99%
“…The high explained variance in VPD reconstruction at the FOD scale further illustrates the controls of VPD on tree-ring δ 18 O (Figure 8). Several studies have shown a positive correlation between Larix tree-ring δ 18 O and VPD [46,47], and have used this relationship to reconstruct past VPD variations [47]. In addition, Larix is sensitive to drought and soil moisture because of low drought tolerance [48].…”
Section: Climate Drivers Of Tree's Physiologymentioning
confidence: 99%
“…In contrast, low VPD leads to reduced water transport into the leaves and thus a reduced supply of nutrients. This marks VPD as an important indicator for plant activity (Novick et al, 2016), which among other things notably affects plant growth (Restaino et al, 2016), forest mortality (Park Williams et al, 2013), drought occurrence (Dai, 2013), crop production (Zhao et al, 2017) and wildfire occurrence (Seager et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is essential to investigate the independent physiological effects of VPD on large-scale vegetation dynamics, which are less explored (Grossiord et al, 2020). So far, first local reconstruction studies have shown the potential of a long-term perspective on VPD (e.g., Liu et al, 2017). For example, Churakova- Sidorova et al (2020) have shown that the recent VPD increase does not yet exceed the maximum values reconstructed during the Medieval Warm Anomaly in Siberia.…”
Section: Introductionmentioning
confidence: 99%